Altered levels of memory T cell subsets and common γc cytokines in Strongyloides stercoralis infection and partial reversal following anthelmintic treatment. - Anuradha Rajamanickam; Saravanan Munisankar; Yukti Bhootra; Chandra Kumar Dolla; Kannan Thiruvengadam; Thomas B Nutman; Subash Babu (Public Library of Science (PLoS), 2018)
CD4+ and CD8+ T cells are central players in immunity to helminth infections. However, the role of T cell subsets in human helminth infections is not well understood. In addition, the common γc cytokines, IL-2, IL-4, IL-7, IL-9 and IL-15 play an important role in the maintenance of these CD4+ and CD8+ T cell subsets.To examine the major T cell subsets and their association with the common γc cytokines, the absolute numbers of CD4+ and CD8+ naïve, central memory, effector memory and effector cells and the plasma levels of IL-2, IL-4, IL-7, IL-9 and IL-15 were measured in Strongyloides stercoralis (Ss) infected (INF, n = 60), helminth-uninfected (UN, n = 58) and in post treatment INF individuals.Ss infection is characterized by significantly increased absolute numbers of naïve and decreased absolute numbers of central and effector memory CD4+ T cells in comparison to UN individuals. No significant difference in the numbers of CD8+ T cell subsets was observed between the groups. The numbers of naïve cells and central memory CD4+ T cells were significantly reversed after anthelmintic treatment. Circulating levels of IL-2, IL-7 and IL-15 were significantly diminished, whereas the levels of IL-4 and IL-9 were significantly increased in INF compared to UN individuals. Following anthelminthic treatment, IL-2, IL-7 and IL-15 levels were significantly increased, while IL-4 and IL-9 levels were significantly decreased. Our data also showed a significant positive correlation between the levels of IL-7 and the numbers of central and effector memory CD4+ T cells.Ss infection is characterized by alterations in the absolute numbers of CD4+ T cell subsets and altered levels of common γc cytokines IL-2, IL-4, IL-7, IL-9 and IL-15; alterations which are partially reversed after anthelmintic treatment.